2018
DOI: 10.14419/ijet.v7i2.29.13813
|View full text |Cite
|
Sign up to set email alerts
|

Communication Style and Communication Competence Of President Jokowi

Abstract: This research would like to see the communication style of president jokowi in connection with the disharmony of his ministers in communicating in public. The problem in this research is; (1) How is President Jokowi's communication style in policy making? (2) How is the communication competency of President Jokowi?. The method used in this research is qualitative by using structural discourse analysis. Data were taken from online news especially detik.com and kompas.com, which is the most popular data provider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The specialized literature told us that writing can be taught with or without technological mediations. However, much of the reviewed research concluded that the inclusion of Information and Communication Technologies (ICT) was fundamental in the development of basic writing skills (Awada et al, 2019;Mohankumar et al, 2018). Especially in response to the expectations of education in the 21st century, these skills were linked to the further development of informational skills, understood as a set of knowledge, skills and values applied to the "search, recovery, analysis, treatment, communication and application of information" (Monereo & Badia, 2012, p. 77).…”
Section: Discussionmentioning
confidence: 99%
“…The specialized literature told us that writing can be taught with or without technological mediations. However, much of the reviewed research concluded that the inclusion of Information and Communication Technologies (ICT) was fundamental in the development of basic writing skills (Awada et al, 2019;Mohankumar et al, 2018). Especially in response to the expectations of education in the 21st century, these skills were linked to the further development of informational skills, understood as a set of knowledge, skills and values applied to the "search, recovery, analysis, treatment, communication and application of information" (Monereo & Badia, 2012, p. 77).…”
Section: Discussionmentioning
confidence: 99%